"I'm Paying, So I Decide": Czech ANO as an Extreme Form of a Business-Firm Party. (November 2016) - Kopeček, Lubomír
Business-firm parties founded on the initiative of a political entrepreneur are a phenomenon of growing importance in contemporary party politics. In practice, these are either commercial companies, whose structure is used for a political project, or new and separate organisations constructed on business principles. This article examines the case of Czech party ANO ("YES"), established by the owner of the Agrofert holding company Andrej Babiš. The party achieved remarkable success in the 2013 Czech general election. The opportunity for ANO's success was provided by strong voter dissatisfaction, reinforced by the scandalous circumstances of the centre-right government's fall. This context created a fertile ground for the introduction of a new entity espousing anti-party, anti-corruption, and anti-political sentiments. In ANO's organisation and functioning, a strengthening of certain traits characteristic of this type of parties is apparent. A robust system for screening party members and representatives has been gradually put into place, and human resources–style techniques of psychological testing were employed at the party's inception. Furthermore, the power in the party has been wholly centralised around the leader, and the party's territorial structures assigned merely service tasks. ANO has also maximised its electoral-professional orientation. The strengthening of the typical traits of a business-firm party can be explained by reference to the party's origin in the business environment and the notions entertained by its leader. In many respects, Babiš's party has brought the organisational model of a business-firm party to its limits.